Long-Term Potentiation of Synaptic Transmission by Synthetic Mast Cell Degranulating (MCD) Peptide - MIKOSHIBA, Katsuhiko; IKENAKA, Kazuhiro; AIMOTO, Saburo; ITO, Ken-ichi; FUJIMOTO, Ichiro; KATO, Hiroshi; HOJO, Hironobu; KONDO, Tetsuro (Seibutsu Butsuri, 1990)
A bee venom, mast cell degranulating peptide (MCD), was synthesized by stepwise formation of the two distinct disulfide bridges. This synthetic peptides with mast cell degrahulating activity MCD induced long-term potentiation (LTP) in the CAl region of hippocampus, while other peptides with mast cell degranulating activity apamin and mastoparan did not. This and other results using derivatives of the synthetic MCD suggest that a rigid structure is required for the LTP induction by MCD. Two antagonists of the N-methyl-D-aspartate (NMDA) receptor, AP5 and MK801, did not block the MCD induced-LTP. Moreover, the efficacy of the synaptic transmission in the slice which had been maximally activated by tetanic stimulation was further potentiated by MCD treatment. These results indicate that two quite distinct pathways for LTP formation exist in the CAl region of the hippocampus.